Implementation of Pancasila Values in Generation Z - Adonis Putra Mahecwara; Tania Dina Antasari; Muhammad Daffa Putra Pratama; Riska Andi Fitriono (CV. Rayyan Dwi Bharata, 2022)
Pancasila is the foundation or guideline for the Indonesian nation as a source of life for Indonesian people, so that in everyday life it is very necessary to apply Pancasila values, Pancasila itself can keep up with the times and can be applied in generations, including Generation Z. live in the era of globalization, which is advanced in technology and information. In this study the aim is to find out the implementation of Pancasila values for generation Z so that they can be applied in everyday life even though information technology is developing rapidly, because in the current era of globalization, generation Z is considered to have forgotten the values pancasila value. The method used is a quantitative method or a descriptive approach to literature study. As students we conducted this research as a form of concern and love for Pancasila as a guideline for Indonesian society.